Case method learning with multicultural approach: The implementation to increase students historical empathy and love for the country - Kurniawanti, Merci Robbi; Wahyuni, Anny; Saputra, Muhammad Adi (Univeritas Papua, 2023)
This research aims to increase historical empathy and love for the student’s country in the history education study program. The case method model was chosen as a solution to answer problems in the field related to the low historical empathy and love for the country of students which is visible during the lecture process. This research is classified as classroom action research which is divided into 3 cycles. In each cycle is divided into four stages, there are plan of action, implementation, observation and reflection. The data collection techniques used were observation, interviews, documentation and literature study. Based on the research results, it can be seen that the case method learning model with a multiculturalism approach in contemporary Indonesian history courses can increase students' historical empathy and love for their country. Students' historical empathy and love for the country have increased in each cycle. The percentage of historical empathy obtained in the cycle is 20.6, in cycle II is 27.6 and in cycle three increased to 35.8. Meanwhile, for love of the country in cycle I, the percentage obtained was 69.6, cycle II 74.2 and cycle III 79.8.